Readers' guide to periodical literature - Cannon, Donald M.; Polewchak, Jane c. (New york : H.W. Wilson, 2010)
"An author subject index to selected general interest periodicals of reference value in libraries."
At head of title: Wilsondisc.
Keywords: Periodicals -- Indexes